American English today : the uses of language - Guth, Hans P.;Schuster, Edgar H. (New York : McGraw Hill Education, 1970)
This volume offers, an organic program in all major areas of english.
Chapter 1. Words -- Chapter 2. Grammar -- Chapter 3. Usage -- Chapter 4. Composition -- Chapter 5. Mechanics -- Chapter 6. Speech -- Chapter 7. Resource units.
Keywords: LANGUAGES